2014
DOI: 10.1073/pnas.1406131111
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans RSD-2 and RSD-6 promote germ cell immortality by maintaining small interfering RNA populations

Abstract: Germ cells are maintained in a pristine non-aging state as they proliferate over generations. Here, we show that a novel function of the Caenorhabditis elegans RNA interference proteins RNAi spreading defective (RSD)-2 and RSD-6 is to promote germ cell immortality at high temperature. rsd mutants cultured at high temperatures became progressively sterile and displayed loss of small interfering RNAs (siRNAs) that target spermatogenesis genes, simple repeats, and transposons. Desilencing of spermatogenesis genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 56 publications
(55 reference statements)
4
43
0
Order By: Relevance
“…For example, an early genetic screen looked for R NAi s preading d efective ( rsd ) genes under the premise that mutants defective in genes required for the spread of RNA to the germline would be capable of silencing in response to dsRNA injected into the germline but not in response to dsRNA ingested from the environment (Tijsterman et al, 2004). While this screen identified alleles of sid-1 (called rsd-8 in the study), it identified additional genes such as rsd-2 and rsd-6 that satisfy the screen criteria but were nevertheless later found to be required for the efficient execution of RNA silencing within cells (Han et al, 2008, Sakaguchi et al, 2014). One possible explanation for the earlier misclassification is that the dosage of dsRNA delivered by injection is far greater than that delivered by ingestion, which makes a mutant with a partial defect in the execution of RNA silencing appear to have a defect in the transport of RNA between cells.…”
Section: Cautionary Talesmentioning
confidence: 99%
“…For example, an early genetic screen looked for R NAi s preading d efective ( rsd ) genes under the premise that mutants defective in genes required for the spread of RNA to the germline would be capable of silencing in response to dsRNA injected into the germline but not in response to dsRNA ingested from the environment (Tijsterman et al, 2004). While this screen identified alleles of sid-1 (called rsd-8 in the study), it identified additional genes such as rsd-2 and rsd-6 that satisfy the screen criteria but were nevertheless later found to be required for the efficient execution of RNA silencing within cells (Han et al, 2008, Sakaguchi et al, 2014). One possible explanation for the earlier misclassification is that the dosage of dsRNA delivered by injection is far greater than that delivered by ingestion, which makes a mutant with a partial defect in the execution of RNA silencing appear to have a defect in the transport of RNA between cells.…”
Section: Cautionary Talesmentioning
confidence: 99%
“…Because RDE-4 promotes the biogenesis of endogenous small RNAs and rde-4 mutants have relatively minor overt phenotypes (11,40,41), we asked whether deficiency for rde-4 affects the lifespan of daf-2 mutants. We found that daf-2; rde-4 double mutant lifespan was not significantly different than that of daf-2 single mutant controls ( Fig 1A, S1 Table, p=1), indicating that the small RNA pathway that can be activated by DAF-16 in prg-1 mutants is dispensable for its function in adult longevity.…”
Section: Resultsmentioning
confidence: 99%
“…A second pathway that promotes germ cell immortality is a genomic silencing pathway where small RNAs associate with Argonaute proteins to promote heterochromatin formation (10)(11)(12). This pathway initiates with the perinuclear Argonaute protein PRG-1, the C. elegans ortholog of Piwi, which localizes to P granules of germ cells and interacts with thousands of 21 nucleotide piRNAs that scan the genome for viruses, transposons or foreign nucleic acids such as man-made transgenes (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Inherited dsRNAs also spread between cells in the progeny to elicit a systemic effect. Consistent with this idea, RNAi spreading defective factors RSD‐2 and RSD‐6 have been found to promote genome silencing and maintain siRNA populations in progeny [Sakaguchi et al., ]. However, whether and how parentally acquired dsRNAs could engage in multigenerational RNAi inheritance requires further investigation because parentally acquired dsRNAs will be quickly diluted over generations.…”
Section: Dsrna the Rnai Spreading Defective (Rsd) Pathway And Intergmentioning
confidence: 97%